Conhecimento astrológico e fronteiras culturais na Alexandria do Principado Romano - Motta, Vinícius de Oliveira da (2019)
This work presents a historiographical and documentary discussion about the city of Alexandria in Egypt during the Roman Principate, considering it as a cultural boundary in the Mediterranean. We sought to analyze how astrological knowledge and Alexandrian astrologers settled in the historical context and how they reflected the cultural influences that made up the Roman Empire and merged into the Egyptian capital. Our point of view is based on discussions of the New Cultural History and Anthropology, mainly aiming to think astrological knowledge as an important cultural modality that developed in the cultural flows between the societies of the old Mediterranean and that took its form in Alexandria. Thus, we try to analyze part of the historical contingencies and cultural conditions in Egypt that propitiated the development of knowledge and institutions in the city. Our sources of research were the texts of the Alexandrian astrologers Claudius Ptolemy and Vettius Valens, respectively the Tetrabiblos and the Anthology, two important astrological treatises of the second century CE, period considered as the pinnacle of the Alexandrian astrology in the Roman Empire. The work is divided into three chapters. We began with a bibliographical survey on Alexandria and its demographic and cultural composition, highlighting some strategies used by Egyptians, Greeks and Romans that contributed to the city becoming a reference in terms of knowledge and, mainly, for the creation and maintenance, for centuries, of teaching and research institutions such as the Royal Library and Mousêion. In the second chapter, we performed a history of astrological knowledge between Mesopotamians, Egyptians and Greeks and discussed the social and cultural conditions that involved the development of the astrological specialty in these societies. We also traced the trajectory of the studied astrologers and presented the works analyzed. In the last chapter we show the importance reached by astrology, becoming a discipline of Egyptian, Hellenistic and Roman basic education, closely related to many other knowledge and practices. We also dealt with the relationship between astrological techniques and popular cults to the daimons, Isis, Serapis and Osiris, and analyzed how the astrologers Ptolemy and Valens embraced in their techniques the ethnic-cultural complexity that characterized Alexandria. In the final chapter we are still dealing with and giving some examples of how the Romans used the astrological concepts and knowledge and the discourses that were produced from them and how our sources reflect the question.